2016
DOI: 10.5935/1415-2762.20160058
|View full text |Cite
|
Sign up to set email alerts
|

Waiting Time for Assistance Using the Machester Triage System in an Emergency Hospital

Abstract: RESUMOO Sistema de Triagem de Manchester (STM) é utilizado em serviços de urgência para determinar prioridade clínica de pacientes, otimizando o tempo de espera para atendimento médico. Estudos que mensurem diferentes tempos de espera para atendimento são escassos. Objetivo: avaliar tempos de espera para atendimento de pacientes em hospital público de urgência. Método: estudo descritivo realizado em hospital público de urgência brasileiro com população de 68.215 prontuários de pacientes atendidos em 2014. Os d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
1
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 11 publications
3
12
1
5
Order By: Relevance
“…Regarding the analyzed time intervals, to our knowledge, only two Brazilian studies (10,18) and one European (19) study carried out such an evaluation. The present study found average time between recording and RC of 7.7 minutes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Regarding the analyzed time intervals, to our knowledge, only two Brazilian studies (10,18) and one European (19) study carried out such an evaluation. The present study found average time between recording and RC of 7.7 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…In a Brazilian study, the average time of 12 minutes was found. However, the maximum time recommended by the MTS is 10 minutes (10,18) . Two other studies observed a median time of 6 minutes for the interval between recording and RC (19)(20) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Still in the case of patients classified in the red category, research shows that, in some emergency services, critically ill patients are generally seen even before opening the hospital registration form, and that triage routine is performed retroactively, after the patient’s clinical stabilization ( 1 , 4 - 5 ) .…”
Section: Introductionmentioning
confidence: 99%